The preliminary application of electromyography in unilateral biportal endoscopy with general anesthesia for lumbar disc herniation - Tang, Shaolong; Liao, Yutian; Pan, Juan; Chen, Dayong; Pan, Dan (Frontiers in Surgery, 2025)
ObjectiveTo investigate the clinical efficacy of electromyography (EMG) in unilateral biportal endoscopy (UBE) with general anesthesia in the treatment of lumbar disc herniation.MethodsA total of 78 patients with lumbar disc herniation were enrolled. They underwent UBE discectomy under general anesthesia, with the entire procedure of EMG monitoring. Recorded potentials were displayed on the monitoring screen, and electromyographic activity was audibly relayed via speakers. Clinical treatment outcomes were assessed using Visual Analog Scale (VAS) and Oswestry Disability Index (ODI).ResultsAll 78 patients successfully completed the procedure, with significant improvement in symptoms postoperatively. Preoperative and 3-month postoperative VAS scores were 4–9 (mean 6.65 ± 1.53) and 0–4 (mean 1.40 ± 1.23), respectively. Preoperative and 3-month postoperative ODI scores were 36–88 (mean 59.56 ± 13.81) and 4–29 (mean 14.82 ± 6.68), respectively, with statistically significant differences (P < 0.05). Abnormal EMG changes, including spike, burst, or tonic electromyographic discharges, occurred in 12 patients during surgery, with an incidence of 15.38%. Ten patients experienced radicular burning pain and abnormal lower limb sensations postoperatively, while two patients had no significant postoperative neuralgia, resulting in a false positive rate of 16.67%. Patients without abnormal EMG responses during surgery had no significant postoperative neuralgia, yielding a false negative rate of zero.ConclusionGeneral anesthesia combined with UBE monitord by intraoperative EMG is a safe and feasible approach for the treatment of lumbar disc herniation.